1996
DOI: 10.1002/hep.510230421
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 ? markedly stimulates nitric oxide formation in the absence of other cytokines or lipopolysaccharide in primary cultured rat hepatocytes but not in Kupffer cells

Abstract: responses. 1 In vivo, NO has been reported to have pro-LPS stimulated NO formation in a dose-dependent manner and induced half-maximal effects at 30 pmol/L. Maxi-tective effects during the inflammation and endotoxemal stimulation was achieved at 12 to 16 hours after the mia associated with hepatic injury. 2 In contrast, NO addition of 1 nmol/L of IL-1b, and was 50-to 60-fold above has also been reported to induce hepatic mitochondrial basal levels in rat hepatocytes. The combined effect of dysfunction both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 2 publications
5
54
0
1
Order By: Relevance
“…Oxide Derivative in Hepatocytes-As reported previously, an inflammatory cytokine IL-1␤ increased levels of nitrite (nitric oxide metabolite) released to the medium in primary cultures of rat hepatocytes, where concentrations for the maximal and half-maximal effects were 1 nM and 30 pM, respectively (8). Simultaneous addition of PAO, a trivalent arsenical compound, inhibited the nitritereleasestimulatedbyIL-1␤inthetime-andconcentrationdependent manner (Fig.…”
Section: Inhibition Of Nitric Oxide Production By Arsinesupporting
confidence: 61%
See 2 more Smart Citations
“…Oxide Derivative in Hepatocytes-As reported previously, an inflammatory cytokine IL-1␤ increased levels of nitrite (nitric oxide metabolite) released to the medium in primary cultures of rat hepatocytes, where concentrations for the maximal and half-maximal effects were 1 nM and 30 pM, respectively (8). Simultaneous addition of PAO, a trivalent arsenical compound, inhibited the nitritereleasestimulatedbyIL-1␤inthetime-andconcentrationdependent manner (Fig.…”
Section: Inhibition Of Nitric Oxide Production By Arsinesupporting
confidence: 61%
“…Induction of iNOS by lipopolysaccharide contributes to the pathogenesis of septic shock (7), leading to organ destruction, including the liver. We (8) and others (9) have reported that a single cytokine interleukin 1␤ (IL-1␤) mimicked the in vivo induction of iNOS in cultured hepatocytes. Other cytokines such as IL-6, tumor necrosis factor ␣ (TNF␣), and interferon ␥ had no effect under the same conditions (8), although a combination of these cytokines and lipopolysaccharide stimulated the nitric oxide production (10,11).…”
Section: Nitric-oxide Synthase (Nos)mentioning
confidence: 98%
See 1 more Smart Citation
“…Pro-inflammatory cytokine IL-1␤ induced a gene expression of iNOS and increased the production of nitric oxide in primary cultures of rat hepatocytes as reported previously. 46,47 Under hypoxic conditions with an Anaeropack system, oxygen concentrations dropped to less than 1% within 1 hour after the introduction of hypoxia. Hypoxia inhibited levels of nitrite (nitric oxide metabolite) released into the medium (Fig.…”
Section: Inhibition Of Nitric Oxide Production By Hypoxia and Heat Inmentioning
confidence: 99%
“…In the liver, LPS and inflammatory cytokines, such as interleukin (IL)-1 and tumour necrosis factor-␣, cause iNOS induction, and then provoke prominent NO production (Nathan 1992;Geller et al 1993). Using primary cultured cells from the rat liver, we and another group have demonstrated that the NO production is induced by IL-1␤ in hepatocytes, whereas NO is produced by LPS in Kupffer cells (Geller et al 1995;Kitade et al 1996). IL-1␤ effectively increases iNOS mRNA, and then NO production in human hepatocytes (Geller et al 1995).…”
Section: Introductionmentioning
confidence: 99%